Ages of major Little Ice Age glacier fluctuations on the southeast Tibetan Plateau derived from tree-ring-based moraine dating - Hochreuther, Philipp; Loibl, David; Wernicke, Jakob; Zhu, Haifeng; Grießinger, Jussi; Bräuning, Achim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
Advances and retreats of glaciers on the Tibetan Plateau (TP) are widely regarded as indicators for climate changes sensitive to macroclimatic forcing mechanisms like the Asian summer monsoon. However, it often remains unclear why some glaciers retreat or advance earlier than others, particularly regarding the timing of the so-called ‘Little Ice Age (LIA) maximum’. Within this study, we present newly acquired tree-ring data from four glacier forefields in the Nyainqêntanglha Range on the southeastern TP and link them to previous studies. Two of the glaciers formed a double-tongue moraine set during the LIA, with trees providing minimum ages for two different major glacier extents. In combination with evidence from a third glacier, three warm phases within the generally cold LIA can be deduced during the first half of the 16th century, and the mid-17th and 18th centuries. This implies the occurrence of three preceding major cold spells. A minor cool phase between 1790 and 1850 marks the end of the LIA on the southeast TP. Minimum ages for beginning retreat from the last major LIA glacial advance differ by only 40 years for all sampled monsoonal temperate valley glaciers in the Nyainqêntanglha Range. This implies a common forcing, whose impact on glacier dynamics is only slightly altered by topographical factors or local climatic conditions. Regression analysis suggests that the delay of the glacier retreat from the maximum extent is mainly related to glacier size, with minor influence of ablation area aspect. All moraine ages highlight intermediate LIA warm phases on the southeast TP corresponding to warm phases on the northern Hemisphere and thus prove monsoonal temperate glaciers to be highly sensitive archives for northern hemispheric climatic conditions.
Keywords: Dendroglaciology; Tibetan Plateau; Glacier history; Tree rings; Moraine dating

Air mass origin signals in δ 18O of tree-ring cellulose revealed by back-trajectory modeling at the monsoonal Tibetan plateau - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (International Journal of Biometeorology, 2017)
Keywords: Backward trajectory; Tibetan plateau; Asian summer monsoon; Tree-ring δ18O

Air mass signals in δ18O of tree-ring cellulose revealed by back-trajectory modeling at the monsoonal Tibetan plateau - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (International Journal of Biometeorology, 2017)
A profound consideration of stable oxygen isotope source water origins is a precondition for an unambiguous palaeoenvironmental interpretation of terrestrial δ18O archives. To stress the influence of air mass origins on widely used δ18O tree-ring chronologies, we conducted correlation analyses between six annually resolved δ18O tree-ring cellulose (δ18OTC) chronologies and mean annual air package origins obtained from backward trajectory modeling. This novel approach has been tested for a transect at the southeastern Tibetan plateau (TP), where air masses with different isotopic composition overlap. Detailed examinations of daily precipitation amounts and monthly precipitation δ18O values (δ18OP ) were conducted with the ERA Interim and Laboratoire de M´et´eorologie Dynamique General Circulation Model (LMDZiso) data, respectively. Particularly the southernmost study sites are influenced by a distinct amount effect. Here, air package origin δ18OTC relations are generally weaker in contrast to our northern located study sites. We found that tree-ring isotope signatures at dry sites with less rain days per year tend tobe influenced stronger by air mass origin than tree-ringisotope values at semi-humid sites. That implies that the local hydroclimate history inferred from δ18OTC archives is better recorded at semi-humid sites.
Keywords: Tree-ring δ18O; Backward trajectory; Asian summer monsoon; Tibetan plateau

Air moisture signals in a stable oxygen isotope chronology of dwarf shrubs from the central Tibetan Plateau - Wernicke, Jakob; Stark, Georg; Wang, Lily; Grießinger, Jussi; Bräuning, Achim (Annals of Botany, 2019)
BACKGROUND AND AIMS: Annually resolved biological climate proxies beyond the altitudinal and latitudinal distribution limit of trees are rare. In such regions, several studies have demonstrated that annual growth rings of dwarf shrubs are suitable proxies for palaeoclimatic investigations. In High Asia, the pioneer work of Liang et al. (Liang E, Lu X, Ren P, Li X, Zhu L, Eckstein D, 2012. Annual increments of juniper dwarf shrubs above the tree line on the central Tibetan Plateau: a useful climatic proxy. Annals of Botany109: 721-728) confirmed the suitability of shrub growth-ring chronologies for palaeoclimatic research. This study presents the first sensitivity study of an annually resolved δ18O time series inferred from Wilson juniper (Juniperus pingii var. wilsonii) from the northern shoreline of lake Nam Co (Tibetan Plateau). METHODS: Based on five individual dwarf shrub discs, a statistically reliable δ18O chronology covering the period 1957-2009 was achieved (expressed population signal = 0.80). Spearman's correlation analysis between the δ18O chronology and climate variables from different sources was applied. In a first step, the suitability of various climate data was evaluated. KEY RESULTS: Examinations of climate-proxy relationships revealed significant negative correlations between the δ18O shrub chronology and summer season moisture variability of the previous and current year. In particular, relative humidity of the previous and current vegetation period significantly determined the proxy variability (ρ = -0.48, P < 0.01). Furthermore, the δ18O variability of the developed shrub chronology significantly coincided with a nearby tree-ring δ18O chronology of the same genus (r = 0.62, P < 0.01). CONCLUSIONS: The δ18O shrub chronology reliably recorded humidity variations in the Nam Co region. The chronology was significantly correlated with a nearby moisture-sensitive tree-ring δ18O chronology, indicating a common climate signal in the two chronologies. This climate signal was likely determined by moisture variations of the Asian summer monsoon. Local climate effects were superimposed on the supra-regional climate signature of the monsoon circulation. Opposing δ18O values between the two chronologies were interpreted as plant-physiological differences during isotopic fractionation processes.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Juniperus pingii var. wilsonii; climate–growth relations; dendrochronology; Tibetan Plateau; δ18O coherence shrub/tree

Assessing moisture sources of precipitation in the Western Pamir Mountains (Tajikistan, Central Asia) using deuterium excess - Juhlke, Tobias; Meier, Christiane; van Geldern, Robert; Vanselow, Kim; Wernicke, Jakob; Baidulloeva, Jamila; Barth, Johannes; Weise, Stephan M. (Tellus B, 2019)
Air moisture of oceanic origin can be subject to long-range transport and could contribute to precipitation at distant places. With ongoing climate change the relationship between water vapour sources and sinks is under constant evolution and plays an important role for water budget assessments. This study analysed monthly integrated and event-based precipitation samples from two field sites in the Western Pamir Mountains (Tajikistan) for stable isotope compositions of oxygen (O-18) and hydrogen (H-2) of water. The aim was to investigate water vapour sources and, in particular, to evaluate contributions of water vapour from the Mediterranean region. The latter has been often postulated as a potential moisture source region for Central Asia. Deuterium excess values (d), that serve as a fingerprint of moisture origin, were below 13 parts per thousand in monthly integrated samples, for most of the year. This indicates a smaller contribution of high Mediterranean moisture (approximate to 20 parts per thousand) to the Western Pamir Mountains than originally expected. A maximum d value of 19 parts per thousand was observed in March, which is not in agreement with the common observation of increased Mediterranean contribution during winter (DJF). A Lagrangian backward trajectory model (HYSPLIT) was applied to infer the general air mass origin for sampled precipitation events. A maximum contribution of western' moisture of 40% was also detected in March, while 40%-60% of moisture that contributed to precipitation events in winter was transported by trajectories that originated from the Northern Indian Ocean.
CRIS-Team WoS Importer:2019-05-07

Dendroecological Perspectives on Climate Change on the Southern Tibetan Plateau - Bräuning, Achim; Grießinger, Jussi; Hochreuther, Philipp; Wernicke, Jakob (Climate Change, Glacier Response, and Vegetation Dynamics in the Himalaya. Contributions Toward Future Earth Initiatives., 2016)
Tree rings are indicators of historic environmental changes and plant response to past and current climate change. Summer temperature reconstructions from maximum latewood density on the southeastern Tibetan plateau (TP) for the past 600 years revealed cool summer temperatures between ca. 1580 and 1790 A.D., corresponding to the “Little Ice Age (LIA).” This period was characterized by several glacier advance periods, with a maximum glacier extent ending around 1740–1780 A.D. and smaller readvance phases during the early nineteenth to late nineteenth century. Stable carbon isotope analyses of tree-ring cellulose indicate species-specific ecophysiological response patterns of trees to environmental conditions related to enhanced atmospheric CO2 levels and drier site conditions which might affect future forest composition. Spatial patterns of altitudinal changes of climate-growth relationships indicate the dominance of different growth-limiting factors in different regions of the TP. In semiarid regions along the western distribution limit of forests, moisture availability during the growing season is most relevant for growth of juniper tree species even in high altitudes. In contrast, warmer temperatures have a stimulating effect on radial growth close to the upper tree limit on the humid eastern TP. These findings are corroborated by first studies of cambial phenology, indicating a stimulating influence of early growing season temperatures on cell formation. In the dry northeastern TP, wet conditions during the main growing season in June are favorable for radial growth. Due to the low number of studies and a long history of human impact on forests, a climate-driven upward shift of the upper tree limit cannot yet clearly be stated. Tree-ring analyses on long-living dwarf shrubs may increase the potential for dendrochronological climate reconstructions beyond the upper limit of tree growth on the TP.
Keywords: Tibetan plateau; Climate reconstruction; Tree rings; Stable isotopes; Dendroecology; Glacier history

Drought signals in tree-ring stable oxygen isotope series of Qilian juniper from the arid northeastern Tibetan Plateau - Qin, Chun; Yang, Bao; Bräuning, Achim; Grießinger, Jussi; Wernicke, Jakob (Global and Planetary Change, 2015)
For the mechanistic understanding of hydroclimate variability, stable oxygen isotopic ratios (δO) of tree-ring α-cellulose can play a key role in paleoclimatic research. On the north-east Tibetan Plateau (TP), a region particularly sensitive to climate change, there exists a distinct lack of δO research in tree-ring archives. The few currently existing tree-ring δO chronologies were obtained by pooling the wood material from the same year from different trees prior to preparation and analysis. Although this method is time and cost efficient, it might impede the analysis of changes within the internal variability of oxygen isotope signals and a deeper understanding of the resulting climate reconstruction. We selected five Qilian juniper (Sabina przewalskii Kom.) trees covering the period 1951-2011 on the north-east TP to investigate the climate signals contained in stable oxygen isotopic composition records obtained using single tree analysis. Although the inter-series correlation between the five individual δO series indicates a highly significant relationship (mean r=0.59, n=59, p=0.01), the five individual δO series show significantly differently mean values. We found significant negative correlations between drought/hydroclimatically triggered climate parameters (PDSI, precipitation) and each of the individual δO series. Spatial correlation maps indicate negative correlation of tree-ring δO and Indian Ocean sea surface temperatures, and inverse correlation patters of moisture conditions on the northern and southern TP. Our results provide a reference for future research on stable oxygen isotope/climate signals in the species S. przewalskii Kom.
Keywords: Hydroclimate; North-east Tibetan plateau; Sabina przewalskii; Stable oxygen isotopes; Wood cellulose

Hydroclimatic variability of the Tibetan Plateau during the past millennium - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lili; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 13: Proceedings of the DENDROSYMPOSIUM 2014 Scientific Technical Report 15/06, GFZ Potsdam, 2015)

Influence of the Indian Ocean Dipole on tree-ring δ18O of monsoonal Southeast Tibet - Hochreuther, Philipp; Wernicke, Jakob; Grießinger, Jussi; Mölg, Thomas; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (Climatic Change, 2016)
We present a newly developed, annually resolved tree-ring cellulose δO chronology for the southeastern Tibetan Plateau (TP) from Sikkim larch (Larix griffithii), spanning between 1684 and 2012. Comparisons with local and regional climate data reveal strong positive correlations with monthly sunshine hours, temperature and daily temperature amplitude as well as strong negative correlations with relative humidity, vapor pressure, rain days per month and cloud cover of August. Relationships with local and regional tree-ring δO chronologies are stable and highly significant. Over the 20th century, we find no long-term climatic trends. This is consistent with other tree-ring δO chronologies of other tree species south of the Himalayas, but contrasts with results from isotope studies north of the Himalayas. This suggests stable macroclimatic flow patterns throughout the last centuries for the southern tree stands. In terms of large-scale climate dynamics, we find evidence of a significant 30-year wave influencing our tree-ring oxygen chronology, most probably induced by the Indian Ocean Dipole and influencing tree-ring oxygen isotope chronologies along the southeastern Himalaya and the southeastern rim of the TP. This pattern is spatially and temporarily consistent among the chronologies and has apparently strengthened during the last century. During periods of strong positive dipole mode activity, the dipole mode index shows positive correlations with the δO of tree-rings on the southeastern TP.

May–June drought reconstruction over the past 821 years on the south-central Tibetan Plateau derived from tree-ring width series - He, Minhui; Bräuning, Achim; Grießinger, Jussi; Hochreuther, Philipp; Wernicke, Jakob (Dendrochronologia, 2018)
Keywords: Tibetan Plateau; Tree-ring width; Drought variability; South Asian summer monsoon

Multi-century humidity reconstructions from the southeastern Tibetan Plateau inferred from tree-ring δ18O - Wernicke, Jakob; Hochreuther, Philipp; Grießinger, Jussi; Zhu, Haifeng; Wang, Lily; Bräuning, Achim (Global and Planetary Change, 2017)
Keywords: Little Ice Age; Tree-ring δ18O; Southeastern Tibetan Plateau; Teleconnections

On the influence of autocorrelation on the significance of wavelet spectral peaks - Hochreuther, Philipp; Wernicke, Jakob; Grießinger, Jussi; Bräuning, Achim (Proceedings of the DENDROSYMPOSIUM 2016, 2017)

Temperature signals in tree-ring oxygen isotope series from the northern slope of the Himalaya - Huang, Ru; Zhu, Haifeng; Liang, Eryuan; Grießinger, Jussi; Wernicke, Jakob; Yu, Wusheng; Hochreuther, Philipp; Risi, Camille; Zeng, Yijian; Fremme, Astrid; Sodemann, Harald; Bräuning, Achim (Earth and Planetary Science Letters, 2019)
Keywords: westerlies; tree ring; South Asian Summer Monsoon; ice core; oxygen isotope; Himalaya

Tree-ring dating of lateral and terminal Little Ice Age moraines of four glaciers in southeast Tibet - Hochreuther, Philipp; Loibl, David; Wernicke, Jakob; Grießinger, Jussi; Zhu, Haifeng; Bräuning, Achim (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 13: Proceedings of the DENDROSYMPOSIUM 2014 Scientific Technical Report 15/06, GFZ Potsdam, 2013)

Variability of summer humidity during the past 800 years on the eastern Tibetan Plateau inferred from δ18O of tree-ring cellulose - Wernicke, Jakob; Grießinger, Jussi; Hochreuther, Philipp; Bräuning, Achim (Climate of the Past, 2015)

Variability of summer humidity during the past 800 years on the eastern Tibetan Plateau inferred from δ18O of tree-ring cellulose - Wernicke, Jakob; Grießinger, Jussi; Hochreuther, Philipp; Bräuning, Achim (Climate of the Past, 2015)
We present an 800-year δ18O chronology from the eastern part of the Tibetan Plateau (TP). The chronology dates back to AD 1193 and was sampled in AD 1996 from living Juniperus tibetica trees. This first long-term tree-ring-based δ18O chronology for eastern Tibet provides a reliable archive for hydroclimatic reconstructions. Highly significant correlations were obtained with hydroclimatic variables (relative humidity, vapour pressure, and precipitation) during the summer season. We applied a linear transfer model to reconstruct summer season relative humidity variations over the past 800 years. More moist conditions prevailed during the termination of the Medieval Warm Period while a systematic shift during the Little Ice Age is not detectable. A distinct trend towards more dry conditions since the 1870s is apparent. The moisture decline weakened around the 1950s but still shows a negative trend. The mid-19th century humidity decrease is in good accordance with several multiproxy hydroclimate reconstructions for south Tibet. However, the pronounced summer relative humidity decline is stronger on the central and eastern TP. Furthermore, the relative humidity at our study site is significantly linked to the relative humidity at large parts of the TP. Therefore, we deduce that the reconstructed relative humidity is mostly controlled by local and mesoscale climatic drivers, although significant connections to the higher troposphere of west-central Asia were observed.
Keywords: Climate variability; Oxygen isotopes; Tibetan plateau; Relative humidity